Cryptochrome-mediated blue-light signal contributes to carotenoids biosynthesis in microalgae - Zhang, Zhongyi; Han, Tianli; Sui, Jikang; Wang, Hui (Frontiers in Microbiology, 2022)
Microalgae are considered as ideal cell factories for producing natural carotenoids which display favorable biological activities. As the most important abiotic factor, light not only provides energy for photosynthetic metabolism, but also regulates numerous biological processes. Blue light is the main wavelength of light that can travel through water. Previous studies have shown that blue light triggered carotenoid accumulation in several microalgae species, but the molecular mechanism remains unclear. Cryptochromes were blue-light-absorbing photoreceptors that have been found in all studied algal genomes. In this study, several different types of cryptochrome genes were cloned from Haematococcus pluvialis and Phaeodactylum tricornutum. Among them, cryptochrome genes HpCRY4 from H. pluvialis and PtCPF1 from P. tricornutum were upregulated under blue light treatment, in correlation with the increase of astaxanthin and fucoxanthin contents. Besides, heterologous expression and gene knockout was performed to verify the function of HpCRY4 and PtCPF1 in regulating carotenoid biosynthesis in microalgae. These results indicate that carotenoid biosynthesis in microalgae promoted by blue light was mediated by cryptochromes as photoreceptors.